Proto-arithmetic abilities in zebrafish (Danio rerio) - Davide Potrich; Lorenza Montel; Gionata Stancher; Greta Baratti; Giorgio Vallortigara; Valeria Anna Sovrano (Heliyon)
The increasing use of zebrafish (Danio rerio) as a model for studying the neural bases of numerical/quantity abilities pushes toward the development of fast and reliable behavioral tasks for this species. Here, we investigated the spontaneous use of proto-arithmetic in quantity discrimination in zebrafish taking advantage of their shoaling behavior. Male fish underwent preference choice tests in which sets of live female conspecifics sequentially disappeared one by one behind one of two opaque identical panels. Fish spontaneously approached the panel occluding the larger set in a “1 vs. 2” comparison, but failed at “2 vs. 3” and “2 vs. 4”. Limited to an overall amount of three elements in the two groups, zebrafish appeared to be able to deal with additions and subtractions, also suggesting the implicit understanding of an “empty set” (zero) concept. The velocity and the sequential/simultaneous presentation of the stimuli affected the spontaneous preference towards the group with the largest quantity.